Topics in modal analysis & testing. Volume 10 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Mains, Michael; Blough, J. R. (Conference proceedings of the Society for Experimental Mechanics series., 2017)
Topics in Modal Analysis & Testing, Volume 10: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the tenth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Modal Analysis, including papers on: Operational Modal & Modal Analysis Applications Experimental Techniques Modal Analysis, Measurements & Parameter Estimation Modal Vectors & Modeling Basics of Modal Analysis Additive Manufacturing & Modal Testing of Printed Parts.